Participation in regulatory agencies in Bahia (Research, Society and Development, 2020)
This article deals with the State Agency for the Regulation of Public Services for Energy, Transport and Communications of Bahia (AGERBA) and the Basic Sanitation Regulatory Agency of the State of Bahia (AGERSA), the only regulatory agencies of the State of Bahia. The proposed objective was to analyze popular participation in these agencies and propose the adoption of the deliberative model as an instrument to legitimize regulatory acts. The research was carried out under the legal-dogmatic methodological aspect, analyzing the current legislation, as well as the legal concepts related to the theme. It is concluded that the deliberative model was adopted by the agencies, but at different levels, making a legislative review necessary to improve popular participation.